Pengembangan Media Pembelajaran Untuk Meningkatkan Unjuk Kerja Siswa Pada Mata Pelajaran Produk Kreatif dan Kewirausahaan - Perkasa, Gigih; Prasetya, Didik Dwi; Marsono, Marsono (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The purpose of this research is to produce the development of running text led P10 learning media that has a level of media validity and improves student performance in creative product and entrepreneurship subjects. In this study researchers took the ADDIE development method which was felt to be simpler, practical and did not require a relatively long time. Based on data analysis and discussion, the results of the validity of the Running Text Led Dot Matrix P10 learning media with Arduino Uno show the validity of the material obtaining a percentage of 82.14% and the validity of the media 90.62% both of which are included in the criteria for a high level of validity and deserve to be applied. improved learning outcomes in the implementation of the pre-test, then the value increased during the implementation of the post-test with the Running Text Led Dot Matrix P10 learning media with Arduino Uno and was able to increase the effectiveness of the learning media on creative and entrepreneurial product subjects.